2010
DOI: 10.1117/12.846521
|View full text |Cite
|
Sign up to set email alerts
|

Processing of metals and dielectric materials with ps-laserpulses: results, strategies, limitations and needs

Abstract: Ultra short (ps, fs) laser pulses are used, when high requirements concerning accuracy, surface roughness, heat affected zone etc. are demanded for surface structuring. Ps-laser systems that are suited to be operated in industrial environments are of great interest for many practical applications. Here results in the field of 3-d structuring (metals and transparent materials), induced processes and structuring of flexible solar cells will be presented. Beside the pulse duration, which is given by the laser sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Similar calculations have been done for a Gaussian shaped beam as emitted by most ultra short pulsed systems (Neuenschwander et al (2012), Neuenschwander et al (2010, Raciukaitis et al (2009)). Again a maximum removal rate per average power (ablation efficiency) is observed:…”
Section: Ablationmentioning
confidence: 86%
See 1 more Smart Citation
“…Similar calculations have been done for a Gaussian shaped beam as emitted by most ultra short pulsed systems (Neuenschwander et al (2012), Neuenschwander et al (2010, Raciukaitis et al (2009)). Again a maximum removal rate per average power (ablation efficiency) is observed:…”
Section: Ablationmentioning
confidence: 86%
“…It has to be pointed out that the maximum value of the removal rate (5) is only obtained at this optimum point. A general expression for the removal rate of a Gaussian beam is also developed by Neuenschwander et al (2010) and Raciukaitis et al (2009) and reads: …”
Section: Ablationmentioning
confidence: 99%
“…It should be large enough to avoid thermal heating and directed material ejections in the trench [17], but small enough to ablate a closed line when the beam is translated across the sample. Recent studies on surface ablation demonstrated that the highest ablation quality can be achieved if the ratio between the pulse distance and the focus radius is set to d p w 0 = v scan (f rep w 0 ) ≈ 1 [27,28]. This criterion could be fulfilled with the present setup at a scan speed of v scan = 1200 mm/s.…”
Section: Methodsmentioning
confidence: 61%
“…It can be clearly seen that there is an optimum peak fluence ϕ 0,opt with a maximum removal rate. This optimum shows the point, where the ablation process is most efficient, which is well known in the literature [1][2][3][4] and be calculated as follow:…”
Section: Introductionmentioning
confidence: 99%